A boomerang-shaped UWB antenna for spectrum sensing. Issue 7 (3rd May 2022) - Qureshi, Ubaid ur Rahman; Maqsood, Moazam; Amin, Muhammad; Maud, Abdur Rahman; Shoaib, Nosherwan
Abstract : A boomerang-shaped ultra wide band (UWB) planar antenna has been presented for spectrum sensing applications. The presented antenna has been built upon a narrow band isotropic antenna design. In order to achieve a wider bandwidth, an exponential profile (similar to log spiral) is used. Simulation results show that the antenna has an impedance bandwidth of 163% (1.3–12 GHz) for VSWR≤2 with good radiation properties. In order to quantify the antenna performance, antenna radiation pattern and efficiency have been compared with previously reported designs. It is shown that the proposed design is able to achieve nearly omnidirectional patterns in more than one planes while achieving a maximum radiation efficiency of 92%. The overall dimensions of the proposed design are 193.6 mm × 196.5  mm. The prototype of the proposed antenna is manufactured using FR4 substrate ( ε r = 4.4, h  = 1.6 mm).